Peacebuilding - Mac Ginty, Roger (London SAGE reference, 2014)
Showcases the main debates and controversies associated with peacebuilding. This title seeks to go beyond a simple explanation of peacebuilding institutions and projects to unpack the ideas and ideologies that underpin the subject.
v. I. Ideas and Foundations -- v. II. Actors -- v. III. Issues -- v. IV. Contexts.
Keywords: Peace-building.; Peace